Influence of direct-fed exogenous fibrolytic enzymes on ruminal fibrolytic activity in sheep - Giraldo L.A.; Tejido M.L.; Ranilla M.J.; Ramos S.; Mantecón A.R.; Carro M.D. (Nutritional and foraging ecology of sheep and goats, 2009)
Six rumen-fistulated Merino sheep were used in a crossover design experiment to evaluate the effects of a direct-fed exogenous fibrolytic enzyme (12 g/d; ENZ) on ruminal fermentation. Endoglucanase and xylanase activities were present in the enzyme preparation. Sheep were fed a mixed grass hay:concentrate (70:30; fresh matter basis) diet at a daily rate of 60 g/kg body weight0.75. After 21 days of the ENZ supplementation, concentrations of NH3-N and short chain fatty acids (SCFA) and enzymatic activities were determined in ruminal samples at 0, 4 and 8 h after feeding. Samples of the grass hay were incubated in situ in the rumen of each sheep to measure dry matter (DM) and neutral detergent fibre (NDF) degradation. ENZ treatment did not affect (P > 0.05) ruminal pH or concentrations of NH3-N and total SCFA at any sampling time. In contrast, at 0 and 4 h after feeding, molar proportion of propionate tended (P < 0.10) to be greater and acetate:propionate ratio tended (P < 0.10) to be lower in ENZ-supplemented sheep. No effects of ENZ (P > 0.10) were detected 8 h after feeding. Both the ruminally insoluble potentially degradable fraction (b) of grass hay DM and its fractional rate of degradation (c) were increased (P < 0.05) by ENZ treatment. Supplementation with ENZ also increased (P = 0.009 to 0.023) effective and potential degradability of grass hay DM and NDF. Ruminal fluid endoglucanase and xylanase activities were greater (P < 0.05) at 4 h post-feeding in ENZ-supplemented sheep than in control animals. ENZ supplementation did not affect (P = 0.151 to 0.815) either exoglucanase or amylase activity at any sampling time.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)